INSTITUTIONAL ANALYSIS OF REVOLVING FUND LOAN (RFL) FOR THE DEVELOPMENT OF COMMUNITY FOREST PLANTATIONS (CFP) - Hendartin, Entin; Nugroho, Bramasto; Kartodihardjo, Hariadi; Darusman, Dudung (Indonesian Journal of Forestry Research, 2011)
The purpose of this study was to formulate effective and efficient institutions of Revolving Fund Loans for Community Forest Plantation development (RFL CFP) in accordance with variation of field conditions. Benchmarking techniques were used to formulate the institution of RFL CFP. For that purpose, Independent of Direct Assistance Rural Agribusiness Development (IDA RAD) from the Ministry of Agriculture was selected as a benchmark as it was good in performance. The study was conducted in three provinces, i.e. Riau, South Kalimantan (November 2008 to April 2009) and West Java (May 2009 to February 2011). Comparative study was used to analyze the institutions based on the agency theory. The results showed that the institutional of RFL CFP have not accomodated the differences in characteristics, perceptions and capacities of the parties. As a result, the institutions have not been able to overcome the risk of moral hazard, adverse selection and high transaction costs. On the other hand, the institution of IDA RADhas a positive impact on agency relationship. High repayments by IDA RADagent and the increasing number of agents each year have proved the impact.